Potential of Stable Carbon and Oxygen Isotope Variations of Speleothems from Andaman Islands, India, for Paleomonsoon Reconstruction. (31st May 2011) - Laskar, Amzad H.; Raghav, S.; Yadava, M. G.; Jani, R. A.; Narayana, A. C.; Ramesh, R.
Abstract : The Indian monsoon activity, coinciding with the Inter-Tropical Convective Zone (ITCZ), progresses from the southern Indian Ocean during the boreal summer and withdraws towards the south in winter. Islands situated to the south of India receive, therefore, the first and last showers of the monsoon; speleothems in such islands have not yet been explored for their potential to reconstruct past monsoon rainfall. Here, we present the first measurements of stable carbon and oxygen isotopic compositions ( δ 13 C and δ 18 O) of a stalagmite collected from the Baratang Island of Andamans, along with new data on δ 18 O of modern monsoon precipitation (May to July 2010). The aim was to detect (i) whether these samples are amenable to dating using 14 C, (ii) whether their oxygen isotopes indicate precipitation under isotopic equilibrium, and (iii) if (i) and (ii) above are true, can we reconstruct monsoon activity during the past few millennia? Our results indicate that while δ 18 O of speleothem does show evidence for precipitation under isotopic equilibrium; dating by 14 C shows inversions due to varying contributions from dead carbon. The present work highlights the problems and prospects of speleothem paleomonsoon research in these islands.